The Influence of Brand Image On Decisions To Purchase Muslim Cash Products (Case Study in Rabbani) - Komara, Nandang; Narimawati, Umi; Syafei, M. Yani (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2024)
This study aims to examine the effect of brand image on consumer purchasing decisions. Brand image is a key element in marketing strategy that can influence consumer preferences and purchasing behavior. In the context of an increasingly competitive market, understanding how brand image affects purchasing decisions is very important for companies. This research uses a quantitative approach with a survey method to collect data from respondents who are involved in purchasing products or services from certain brands. The results of this study reveal that brand image has a significant influence on consumer purchasing decisions. Respondents tend to be more inclined to choose brands with a positive image, which provides a sense of trust and expected quality. In addition, brand image is also proven to influence customer loyalty, which in turn can have a positive impact on the company's long-term revenue.